Effects of antihelminthic treatment on cell-mediated immunity in Gentoo penguin chicks - Bertellotti, Néstor Marcelo; D'amico, Veronica Laura; Palacios, María Gabriela; Barbosa, Andrés; Coria, Néstor (Polar Biology)
Intestinal parasites suppose a cost to hosts as they compete directly for nutritional resources. Therefore, hosts must defend themselves against intestinal parasites by mounting an immune response. Many penguin species acquire parasites through their diet and transfer these parasites to their chicks when feeding them. High parasite loads in penguin chicks could have effects on their growth and body condition, and ultimately on their survival. Here, we evaluated the effect of parasites on the cell-mediated immune system in Gentoo penguin (Pygoscelis papua) chicks at Stranger Point (25 de Mayo/King George Island, South Shetland Islands). To this end, 12 chicks were experimentally deparasitised with a mixture of anthelminthic drugs (Albendazole and Praziquantel), whereas 10 others were kept as control. We measured cutaneous cell-mediated immunity in response to immunization with phytohemagglutinin (PHA). We also analyzed the leukocyte profile in both treated and control groups before and after the treatment. After the treatment, deparasitised birds showed larger foot-web swelling in response to PHA injection than control birds. Deparasitised penguins also showed lower eosinophil and monocyte counts than controls, whereas heterophils, lymphocytes, and total white blood cell counts did not differ between groups. Our results suggest that Gentoo penguin chicks parasitized with intestinal parasites suffer a cost in terms of reduced cell-mediated immune responses that could ultimately affect their survival. Fil: Bertellotti, Néstor Marcelo. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: D'amico, Veronica Laura. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Palacios, María Gabriela. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Nacional Patagónico; Argentina Fil: Barbosa, Andrés. Consejo Superior de Investigaciones Cientificas. Museo Nacional de Ciencias Naturales; España Fil: ...